2020
DOI: 10.3390/su12031153
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Climate Change and Different Crop Rotation Scenarios on Groundwater Nitrate Concentrations in a Sandy Aquifer

Abstract: Nitrate in groundwater is a major concern in agricultural sub-watersheds. This study assessed the impacts of future climate and agricultural land use changes on groundwater nitrate concentrations in an agricultural sub-watershed (Norfolk site) in southern Ontario, Canada. A fully integrated hydrologic model (HydroGeoSphere) was used in combination with the root zone water quality model (RZWQM2) (shallow zone) to develop water flow and nitrate transport models. Three climate change models and three crop rotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…To sum up, positive climate policies to address greenhouse gas emission controls are important to mitigate increases in TDN fluxes in the future, and more strict management of agricultural land for non-point source control will likely be needed, particularly during the high-flow periods in the summer, to avoid extreme events. It is necessary to project flexible strategies facing the changing climate status in the future to realize a dynamic best management practice including integrated measures [62,63], such as limits on crop fertilization, matching of the timing of fertilizer-to-crop demand, conservation tillage, terraces, and diversions to reduce soil and organic N loss, plant buffer structures, constructed wetlands, and so on.…”
Section: Changes In Pollution Source Apportionmentsmentioning
confidence: 99%
“…To sum up, positive climate policies to address greenhouse gas emission controls are important to mitigate increases in TDN fluxes in the future, and more strict management of agricultural land for non-point source control will likely be needed, particularly during the high-flow periods in the summer, to avoid extreme events. It is necessary to project flexible strategies facing the changing climate status in the future to realize a dynamic best management practice including integrated measures [62,63], such as limits on crop fertilization, matching of the timing of fertilizer-to-crop demand, conservation tillage, terraces, and diversions to reduce soil and organic N loss, plant buffer structures, constructed wetlands, and so on.…”
Section: Changes In Pollution Source Apportionmentsmentioning
confidence: 99%
“…In a study using SWAT model, [70], found that annual P loading would decrease in the future from a watershed in Lake Erie basin due to increased evapotranspiration and decreased snowfall. On the other hand, [14,18,19,68,71,72] all found that nutrient losses may increase in future in Ontario and Quebec watersheds.…”
Section: Effects Of Climate Change On Tile Discharge and Nitrogen Yieldsmentioning
confidence: 99%
“…In Canada mainly watershed-scale studies on impacts of climate change on water resources have been completed by [10][11][12][13][14]. In their study on a watershed in Quebec, [10], simulated future streamflows finding a slight decrease in annual runoff.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is transported from the soil into the groundwater by leaching (Brillard et al ., 2015). Leaching is increased by heavy rainfall and intensive irrigation, both of which will increase with global warming (Zhou et al ., 2010; Green and Anapalli, 2018; Saleem et al ., 2020). In addition to increasing the flow of water through the soil, global warming may affect the diversity of bacteria (Classen et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%